Coping Styles among College Students During COVID-19 Pandemic - Pearl Theniel Escultor; Roselyn Galinato; Roselyn Labadan; Lynvin Liwa; Felix E. Arcilla Jr. (RIRAI Publisher, 2022)
Coping styles are essential for those with mental health problems during the COVID-19 pandemic. This could result in either positive or negative mental health outcomes. It includes cognitive and behavioral efforts used by an individual to solve problems and reduce stress caused by these problems. This paper explores the coping styles among college students during the COVID-19 pandemic. The researchers utilized a descriptive-quantitative research design to identify the coping styles used by BSED students in the new normal due to the COVID-19 pandemic. The respondents were 101 BSED English Students from the second year to the fourth year. The survey questionnaire was used as a data-gathering instrument in the quantitative approach. Based on the findings of the study, the coping styles are moderately used by the BSED students. This means the students practiced coping styles sometimes during the COVID-19 pandemic. In addition, it indicated that students' most popular coping styles, such as seeking social support and avoidance, followed by mental disengagement and humanitarian. The study was anchored on the theory of Lazarus and Folkman (1984), which stated that a person's conscious and unconscious efforts solve problems and relieve stress. To help students cope with the stress of the pandemic and build resiliency, the school should offer stress management workshops and webinars. The students require assistance from the school. These stress management training sessions aim to recognize common emotions and issues associated with the ongoing pandemic.